Exploring Nitric Oxide as a Regulator in Salt Tolerance: Insights into Photosynthetic Efficiency in Maize - Georgi D. Rashkov; Martin A. Stefanov; Ekaterina K. Yotsova; Preslava B. Borisova; Anelia G. Dobrikova; Emilia L. Apostolova (Plants, 2024)
The growing issue of salinity is a significant threat to global agriculture, affecting diverse regions worldwide. Nitric oxide (NO) serves as an essential signal molecule in regulating photosynthetic performance under physiological and stress conditions. The present study reveals the protective effects of different concentrations (0–300 µM) of sodium nitroprusside (SNP, a donor of NO) on the functions of the main complexes within the photosynthetic apparatus of maize (Zea mays L. Kerala) under salt stress (150 mM NaCl). The data showed that SNP alleviates salt-induced oxidative stress and prevents changes in the fluidity of thylakoid membranes (Laurdan GP) and energy redistribution between the two photosystems (77K chlorophyll fluorescence ratio F735/F685). Chlorophyll fluorescence measurements demonstrated that the foliar spray with SNP under salt stress prevents the decline of photosystem II (PSII) open reaction centers (qP) and improves their efficiency (Φexc), thereby influencing QA− reoxidation. The data also revealed that SNP protects the rate constants for two pathways of QA− reoxidation (k1 and k2) from the changes caused by NaCl treatment alone. Additionally, there is a predominance of QA− interaction with plastoquinone in comparison to the recombination of electrons in QA QB− with the oxygen-evolving complex (OEC). The analysis of flash oxygen evolution showed that SNP treatment prevents a salt-induced 10% increase in PSII centers in the S0 state, i.e., protects the initial S0–S1 state distribution, and the modification of the Mn cluster in the OEC. Moreover, this study demonstrates that SNP-induced defense occurs on both the donor and acceptor sides of the PSII, leading to the protection of overall photosystems performance (PIABS) and efficient electron transfer from the PSII donor side to the reduction of PSI end electron acceptors (PItotal). This study clearly shows that the optimal protection under salt stress occurs at approximately 50–63 nmoles NO/g FW in leaves, corresponding to foliar spray with 50–150 µM SNP.